Compilation of sourcing model based on supplier selection criteria - A case study at Ellos - Nilsson, Sofie; Talimy, Saba; Matuka, Gloria (My University, 2016)
Increased globalisation has enabled companies to source for material in various ways, creating a variety of sourcing strategies. It is a challenge to obtain a supplier that can provide the right products to the right cost, at the right quantity and quality, at the right time. In a quest for lower cost, many companies choose to source in the far east which in turn leads to longer lead times, more insecurity with transportation and planning making it more difficult to achieve the right product, at the right cost, time and quantity. The purchasing department usually has to deal with these challenges, which many times are conflicting, a lower and desirable purchasing price may result in too longer lead times when selecting suppliers and a trade-off is needed. In order to obtain the right supplier, there are varieties of methods that can be used during the supplier selection that place selection criteria into consideration in order to attain the company's selection needs. Companies are usually focused on cost and although it is an important factor, it is important to incorporate other factors especially in the fashion market that is fast changing. Supplier selection is an essential activity that is not well studied within the fashion industry. This thesis serves as an example of utilizing quantitative and qualitative factors when evaluating suppliers. It could be of good value for companies that are interested in shifting their supply source. The purpose of this thesis has been to investigate selection criteria for supplier selection and develop a sourcing model for the selection of suppliers for a Swedish home shopping and ecommerce company within apparel and home textile, Ellos. The developed sourcing model has been applied in a case study conducted at the current company for two identical products sourced from one supplier in Turkey respectively China. The sourcing model is of great importance for Ellos as their focus has been mainly on Cost of Goods Sold (COGS). Due to the cost focus Ellos has a major part of their supplier base located in low cost countries in East Asia. In order for Ellos to stay competitive on the market Ellos has to widen their focus and also include other criteria when evaluating suppliers. By doing so the most suitable choice can be obtained. This is also important to other companies for the same reasons due to the focus on lowering cost and not analysing the total cost within the supply chain. The scope considered the clothing part at Ellos and the sourcing model was designed for this section of the company. The model was designed with the supplier selection criteria suited for Ellos own brand of clothing section. This scope was due to that the monetary value is largest within this area of Ellos Group. The sourcing model that was established consists of both Total Cost of Ownership and Analytic Hierarchy Process. A combination of both models resulted in a cost and benefits diagram, compiling an overall combined view of the qualitative and quantitative factors regarding supplier options. The cost and benefits diagram shows that it is beneficial for Ellos to source locally, from Turkey, when it comes to the two fast fashion products.
Keywords: Övrig industriell teknik och ekonomi; Transport; Other industrial engineering and economics; Transport